Innovative breeding strategies in groundnut for climate resilience: A review - Sabitha, Savadamuthu; Utharasu, Subramaniam; Amudha , Kailappan; Sakthivel, Nalliappan; Sivasakthivelan, Panneerselvam (Plant Science Today, 2025)
Peanut (Arachis hypogaea) is an important oilseed crop for food and economic security, especially in tropical and subtropical regions. However, climate change such as rising temperatures, variations in rainfall patterns and increased infection rates of pests and diseases poses a significant threat to production in many regions, though the degree of impact may vary depending on local conditions. Advancements in breeding, biotechnology methods and agronomic practices are essential to ensure sustainable peanut cultivation. This review emphasizes that by utilizing the wild genetic resources with advanced technologies to develop climate-resilient peanut varieties. Traditional breeding methods, including hybridization and mass selection, are integrated with modern approaches like Marker-Assisted Selection (MAS), Genomic Selection (GS) and High-Throughput Phenotyping (HTP) helps to produce a peanut variety with high yielding variety with tolerances to biotic and abiotic stress. Additionally, CRISPR-Cas9 and gene-editing tools enable precise improvements for stress tolerance, paving the way for sustainable groundnut production under changing climatic conditions. Moreover, digital tools such as remote sensing and predictive climate models help the breeding program to develop a variety to specific agro-climatic zones. By adopting these innovations, it is possible to enhance the adaptive capacity of groundnut while minimizing resource inputs. Despite these advanced techniques, challenges remain because groundnut has low genetic diversity and the need for region-specific solutions. This comprehensive approach aims to improve peanut production from the adverse effects of climate change, ensure food security and support the livelihoods of millions of smallholder farmers worldwide.